KAJIAN MUTU SELAMA PENYIMPANAN READY TO EAT SIE REUBOH DALAM KEMASAN ALUMUNIUM FOIL - Hasni, Dian; Nilda, Cut; Yusriana, Yusriana (Politeknik ATI Padang, 2022)
Traditional food is one of the regional tourist attractions, so its quality needs to be improved through increasing shelf life and attractive packaging. Sie reuboh is processed meat with a traditional recipe typical of Aceh Besar. This menu is a festival menu, which means beef boiled together with lard, palm vinegar and spices. The addition of vinegar makes the taste of sie reuboh very distinctive and also increases its shelf life at room temperature. Therefore, this research examines the potential of ready to eat (RTE) sie reuboh by observing changes in quality after being stored for 29 days packaged in aluminum foil packaging at refrigerated room temperature (25-27°C) and refrigerator temperature (5-8°C). The quality parameters observed were water content, pH, TBA value and sensory quality of sie reuboh every week (0, 8, 15, 22 and 29 days of storage). The test results showed that during 29 days of storage, there was a decrease in pH and an increase in TBA values, water content and total microbial fluctuations. Observation results showed that sie reuboh stored at a temperature of 5-8°C had better quality after storage for 29 days than that stored at a temperature of 25-27°C.